The Potential of the Socio-Demographic Profile of the Visitor in the Museum’s Product Strategy - LUKÁČ, Michal; CAGÁŇOVÁ, Dagmar; MATUŠÍKOVÁ, Daniela; GANOBČÍK, Ján; LITOMERICKÝ, Ing. Juraj (Journal of Ecohumanism, 2024)
One of the types of cultural sector institutions with a solid potential to use modern management methods are organisations dealing with cultural heritage management, such as castle museums. Today, however, these cathedrals of cultural tourism have to face the pressures of economic and social change to build public authority and recognition, but most importantly, to create interest and an attractive offer for their existing audiences and a hitherto unreached public. The present article aims to develop a systematic review of empirical experiences in the socio-demographic profile of visitors to selected castle museums, to identify untapped potential in the segmentation of museum audiences and to derive propositions for individual solutions aimed at increasing the attendance of selected castle museums. We used a triplet of separated Chi-square tests for each period to identify the socio-demographic profile. Non-parametric Kruskal-Wallis one-way ANOVA (Analysis of Variance) was used to test for differences in ordinal variables (age and education of visitors). In addition to the individual results for each single museum partially, we can identify through the most frequent, most represented and periodically repeated responses the typical visitor profile of the Castle Castle Museums as follows: female, 31 – 45 years old, secondary education with a high school diploma, working as an executive secondary educated professional employee. Such findings could be helpful in the future when creating so-called tailor-made products for the visitor.